Cost comparison across heart failure patients with reduced and preserved ejection fractions: Analyses of inpatient decompensated heart failure admissions. (15th June 2018) - Olchanski, Natalia; Vest, Amanda R.; Cohen, Joshua T.; Neumann, Peter J.; DeNofrio, David
Abstract: Background: Heart failure (HF) is the leading cause of inpatient admissions in the US for adults aged over 65 years and accounts for more than $17 billion in Medicare expenditures annually. There are limited published data on factors influencing expenditure and the relationship between cost and hospital length of stay. We sought to describe institutional costs of HF hospitalization, as well as demographic and clinical predictors of higher hospitalization costs in an academic hospital setting. Methods and results: Demographic and clinical information was collected retrospectively for 564 unique consecutive patients with a decompensated HF admission during 2010–2013. Forty-six percent had a baseline LVEF >40%, categorized as HF with preserved ejection fraction (HFpEF). Forty-three percent were female and the mean age was 71 years. Patients with reduced ejection fraction (HFrEF) were predominantly male, younger and had a lower burden of baseline comorbidities than HFpEF patients. Length of stay was longer for HFrEF (median 4 days) than HFpEF (median 3 days, p  = 0.01). Mean total hospitalization cost was $9521. Mean costs trended higher for HFrEF patients than for HFpEF patients ($10, 286 versus $8858, p  = 0.07). Room and board contributed more than half of all costs. Conclusions: In this single-center study, we observed a trend towards higher HF hospitalization costs for patients with HFrEF, compared to HFpEF, even though patients with HFpEF are older and had more comorbid conditions. Costs were largely driven by length of stay, with higher heart rate at admission, lower systolic blood pressure, and higher creatinine associated with higher inpatient costs. Highlights: Patients with HFpEF were older and had more comorbid conditions than those with reduced EF Mean costs trended higher for HFrEF patients than for HFpEF patients Length of stay was longer for HFrEF than HFpEF Room and board contributed more than half of all hospital stay costs